analysis of archaeobotanical material from the site of Pampa animas valley Huaura, Peru, season 2006 - Van Dalen Luna, Pieter Dennis (2013)
It has been realized an archaeobotanic analysis of Pampa de Animas site, Huaura valley, Lima, from I and II sectors, using the comparative method and contrast of modern literature. The high density of remains of plants identified in several cultural levels at site show that diet of ancient human people of Huaura and Chancay Valleys had principally agricultural product, confirming that the agriculture was the economic base of these people, as: corn, bean, squash, gourd, achira, habas, and others. The same products cultivated during the Middle Horizon at Huaura Valley, would follow until de Spaniard invasion.